Income and asset poverty among pastoralists in northern Kenya - Mburu, Samuel; Otterbach, Steffen; Sousa-Poza, Alfonso; Mude, Andrew G. (Informa UK Limited, 2017)
In this study we use household panel data collected in Marsabit district of Northern Kenya, to analyse the patterns of livelihood sources and poverty among pastoralists in that area. We estimate income poverty using imputed household income relative to the adjusted poverty line and asset poverty using a regression-based asset index and tropical livestock units (TLU) per capita. Our results indicate that keeping livestock is still the pastoralists’ main source of livelihood, although there is a notable trend of increasing livelihood diversification, especially among livestock-poor households. The majority of households (over 70%) are both income and livestock-poor with few having escaped poverty within the five-year study period. Disaggregating income and asset poverty also reveals an increasing trend of both structurally poor and stochastically nonpoor households. The findings show that the TLU-based asset poverty is a more appropriate measure of asset poverty in a pastoral setting.